IMPROVING EARLY CHILDHOOD TEACHERS’ SKILLS THROUGH STORY TELLING WORKSHOP - Yanuarsari, Revita; Muchtar, Hendi Suhendraya (PEOPLE: International Journal of Social Sciences, 2016)
Education stimulation for children can be given from cognitive, affective and psychomotor aspects. The stimulus must be given by considering appropriate strategies and learning methods which is in accordance with early childhood development and learning principles. Early childhood’s teacher should be able to teach their students appropriately based on children’s development. One way to optimize the teachers’ skills is by equipping them with many skills through trainings, one of which is storytelling training. Early childhood teacher need to have the ability to deliver and create story that contain moral value. Through storytelling, early childhood teachers can impart knowledge and inculcate noble character and develop creativity in effective and enjoyable ways. Based on researchers’ observation in Bandung regency many early childhood teachers do not have varied skills in conveying story to the children. To solve the problem, the researchers conduct story telling workshop for early childhood’s teachers in Bandung regency. The workshop consists of three stages those are pre, ongoing, and post training. The result shows that the workshop increases the participants’ ability in delivering stories to the children. After the workshop participant feel more confident because they could implement many techniques and use some media in delivering the story.